In vitro models as tools for screening treatment options of head and neck cancer - Seliger, Barbara; Al-Samadi, Ahmed; Yang, Bo; Salo, Tuula; Wickenhauser, Claudia (Frontiers in Medicine, 2022)
Various in vitro models using primary and established 2- and 3-dimensional cultures, multicellular tumor spheroids, standardized tumor slice cultures, tumor organoids and microfluidic systems obtained from tumor lesions/ biopsies of head and neck cancer (HNC) have been employed for exploring and monitoring treatment options. All of these in vitro models are to a different degree able to capture the diversity of tumors, recapitulate the disease genetically, histologically and functionally and retain their tumorigenic potential upon xenotransplantation. The models were used for the characterization of the malignant features of the tumors and for in vitro screens of drugs either approved for the treatment of HNC, including chemotherapy and radiotherapy as well as recently developed targeted therapies and immunotherapies, or for novel treatments not yet licensed for these tumor entities. The implementation of the best suitable model will enlarge our knowledge of the oncogenic properties of HNC, expand the drug repertoire and help to develop individually tailored treatment strategies resulting in the translation of these findings into the clinic. This review summarizes the different approaches using preclinical in vitro systems with their advantages and disadvantages and their implementation as preclinical platforms to predict disease course, evaluate biomarkers and test therapy efficacy.